2024
DOI: 10.3390/foods13071015
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Effects of Cold Atmospheric Plasma on the Natural Microbiota and Quality of Pork during Storage

Yelyzaveta K. Oliinychenko,
Sotirios I. Ekonomou,
Brijesh K. Tiwari
et al.

Abstract: Cold atmospheric plasma (CAP) is a novel non-thermal technology with significant potential for use in meat processing to prolong shelf life. The objective of the study was to evaluate the efficiency of CAP treatment on the natural microbiota and quality traits of pork stored for 8 days at 4 °C. CAP treatment was applied by employing piezoelectric direct discharge technology to treat pork samples for 0, 3, 6, and 9 min. Reductions of approximately 0.8–1.7 log CFU/g were observed in total viable counts (TVC) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…This study adds crucial knowledge to the field of food safety, particularly in using gas plasma technology for toxin degradation. Previous studies have demonstrated the potential of plasma technology in inactivating various pathogens and toxins [ 42 , 43 ]. For example, a review article written by Kutasi et al [ 44 ] highlighted the challenges and approaches towards inactivating aflatoxins using UV radiation and pulsed light treatment, ammoniation, ozonation, and gas plasma.…”
Section: Discussionmentioning
confidence: 99%
“…This study adds crucial knowledge to the field of food safety, particularly in using gas plasma technology for toxin degradation. Previous studies have demonstrated the potential of plasma technology in inactivating various pathogens and toxins [ 42 , 43 ]. For example, a review article written by Kutasi et al [ 44 ] highlighted the challenges and approaches towards inactivating aflatoxins using UV radiation and pulsed light treatment, ammoniation, ozonation, and gas plasma.…”
Section: Discussionmentioning
confidence: 99%